White wine light-strike fault: A comparison between flint and green glass bottles under the typical supermarket conditions. (June 2020) - Arapitsas, Panagiotis; Dalledonne, Stefano; Scholz, Matthias; Catapano, Antonio; Carlin, Silvia; Mattivi, Fulvio
Highlights: The light-strike wine fault might have more than one cause. Green glass bottles can provide a good protection up to 50 days. Light-strike is mainly light exposure dependent and temperature does not seems critical. Locate flint glass bottled white wines on the bottom shelf could provide few extra days of protection. A limit could be set up to 20–30 UVI of transmitted through the glass UV light. Abstract: White wines from two vintages were bottled in green and flint glass bottles and stored under typical supermarket shelf conditions. Light-strike fault, colour changes, light and temperature exposure were monitored up to 50 days. In general, green glass bottles secured wine quality for the tested period. Only a few flint glass bottled wines developed a fault due to light-strike after 1–2 days of supermarket shelf life, but all developed the fault after 20–40 days; so we considered the possibility of two mechanisms causing the problem. Flint-glass bottled wines stored on the bottom shelf developed the defect only slightly later compared with the wines on the top shelf. Moreover, storing the wines in dark and cold after a period of exposure to light did not eliminate the fault, indicating that the defect is probably additive. Monitoring the amount of light to which wines are exposed could prevent the fault.